A Canadian Perspective on the American South: Shreve Mccannon and the Construction of History in Faulkner’s Absalom, Absalom! - AlMalki, Afaf Abdullah Ahmed (International Journal of Language and Literary Studies, 2026)
This paper examines William Faulkner’s Absalom, Absalom! (1936) through the lens of Shreve McCannon, Quentin Compson’s Canadian roommate at Harvard, arguing that Shreve’s outsider perspective, rooted in Canada’s historical role as an abolitionist refuge and moral counterpoint to American slavery, serves as a transformative force in the novel’s construction of Southern history. As a detached Northern rationalist unencumbered by regional loyalties or emotional inheritance, Shreve contrasts sharply with Quentin’s traumatic entanglement in the South’s racial legacy, enabling a critical interrogation of the Sutpen saga that Southern narrators cannot achieve alone. Through their collaborative reconstruction of Thomas Sutpen’s story, particularly in revealing Charles Bon’s mixed-race ancestry as the tragic core, Shreve’s probing questions and logical speculations compel confrontation with repressed racial truths and mythic distortions that sustain Southern identity. The analysis finds that Faulkner strategically deploys Shreve’s Canadian viewpoint to transform the narrative into a hemispheric dialogue on historical reckoning, demonstrating that authentic engagement with a traumatic past requires the tense interplay of insider emotion and outsider detachment. Ultimately, Shreve functions as a narrative solvent, dissolving biased Southern mythologies and illustrating the collective, dialogic labour necessary for confronting racial violence and historical guilt. This reading highlights the novel’s modernist epistemology while contributing to Faulkner studies by foregrounding the under-examined transnational significance of Canada as a symbolic space of moral clarity and continental contrast.